Keller’s arthroplasty with proximal metatarsal opening wedge osteotomy in treating severe Hallux Valgus deformity : surgical techniques and case report - Jurdana, Hari (Array, 2009)
Abstract: The paper presents an operative technique proposed for treating severe Hallux Valgus deformity with arthrosis of the first metatarsal joint in elderly people. The procedure consists of the Keller’s arthroplasty in combination with basal osteotomy of the first metatarsal bone, whereby the head of the metatarsal is displaced laterally and plantarward. The osteotomy is fixed with a reconstructive plate. The results show a significant improvement in the hallux valgus angle, the first metatarsal angle, as well as in the plantar pressure distribution